Making gender–work practicable: situating men's reconstruction of 'women's job' in a Swedish supermarket's micro-politics. Issue 4 (2nd April 2016) - Johansson, Kristina
Abstract : Based on empirical data from one Swedish supermarket, this article argues that men's reconstructing of 'women's work' in accordance with a masculinised sense of self what Simpson (2004, 'Masculinity at Work: The Experience of Men in Female Dominated Occupations', Work, Employment & Society 18, no 2: 349–368) calls 'gender–work' is not limited to individual men's perceptions and creations of self. Rather, by investigating the gendered boundary work in which the manager and other workers engage, this study shows how these reconstructions are legitimised and made practicable by organisational micro-politics. By emphasising the specific skills required by 'their' department – produce – the male workers distanced themselves from the routine and standardised stocking that dominated the work performed at the supermarket. This notion that working in the produce department required specialised knowledge was legitimised by the manager and the organisation of work at the supermarket. While at times, other workers (most of them women) challenged the boundaries of the produce department, they simultaneously re-established those boundaries by glossing over potential conflicts and maintaining equal treatment existed within the organisation.